Exploring total quality management applications under uncertainty: A research agenda for the shipping industry. Issue 4 (December 2016) - Pantouvakis, Angelos; Psomas, Evangelos
Abstract The present study explores total quality management (TQM) implementation in shipping companies by identifying the TQM practices adopted by them as well as the respective TQM management results. Determining the relationships among TQM factors and results, especially under the moderating effect of market or environmental uncertainty, is also an aim of this study. Evidence is drawn using data from 87 major shipping companies based in Piraeus/Greece, and exploratory factor analyses are carried out to extract five TQM practices and four TQM results latent factors. The TQM factors that significantly influence quality management results are further determined through multiple linear regression analyses. Results reveal a set of strategic choices focusing not only on the strict implementation of ISM rules and procedures, but also toward a continuous change in management and leadership culture aiming to achieve better results. Finally when uncertain environments are experienced or perceived, a shift toward a more agile management approach is a prerequisite for success. This article describes a reliable and valid TQM model applied in the shipping service sector and a way for shipping companies to improve their business performance.